Memorandum Concerning UN Action on Hungary - Héderváry, Claire de (1958)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. According to this memorandum, the General Assembly of the United Nations has adopted nine political resolutions on Soviet aggression against Hungary, but has failed to take any action to enforce its resolutions.